2001
DOI: 10.1128/iai.69.12.7933-7936.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the sigB Operon in Staphylococcus epidermidis : Construction and Characterization of a sigB Deletion Mutant

Abstract: The role of the alternative sigma factor B in Staphylococcus epidermidis was investigated by the construction, complementation, and characterization of a sigB deletion mutant. Electrophoretic analyses confirmed a profound influence of B on the expression of exoproteins and cytoplasmic proteins. Detailed investigation revealed reduced lipase and enhanced protease activity in the B mutant. Furthermore, no significant influence of B on heterologous biofilm formation or on the activity of the global regulator agr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In contrast, Kies et al (35) demonstrated that the expression of the icaADBC locus in trans from plasmid pCN27 (31) in a sigB mutant in the icaADBC-negative genetic background of S. epidermidis Tü3298 was able to form large cell clusters. These findings lead to the conclusion that the B -independent biofilm formation of this strain might therefore be explained by a nonfunctional RsbU-mediated regulatory pathway (35). However, the icaR gene, encoding a recently characterized negative regulator of icaADBC transcription (14), is lacking in plasmid pCN27, which could also explain the observed biofilm-positive phenotype in the sigB mutant.…”
mentioning
confidence: 72%
“…In contrast, Kies et al (35) demonstrated that the expression of the icaADBC locus in trans from plasmid pCN27 (31) in a sigB mutant in the icaADBC-negative genetic background of S. epidermidis Tü3298 was able to form large cell clusters. These findings lead to the conclusion that the B -independent biofilm formation of this strain might therefore be explained by a nonfunctional RsbU-mediated regulatory pathway (35). However, the icaR gene, encoding a recently characterized negative regulator of icaADBC transcription (14), is lacking in plasmid pCN27, which could also explain the observed biofilm-positive phenotype in the sigB mutant.…”
mentioning
confidence: 72%
“…Similarly, lipase gene expression is differentially regulated by the alternative sigma factor SigB in the closely related species Staphylococcus aureus and Staphylococcus epidermidis (27). While lipase secretion is elevated in an S. aureus sigB-null mutant (30), secretion of processed lipase in an S. epidermidis sigB-null mutant is reduced significantly (28).…”
Section: Discussionmentioning
confidence: 99%
“…1A); however, B serves different functions in the two species. Processing of lipase, a virulence factor, is dependent on B in S. epidermidis (102), while in S. aureus, lipase production is higher in a sigB mutant than in the wild-type strain (114). Multiple studies of B and S. epidermidis virulence suggest that B 's effects are mediated primarily through its influence on biofilm formation in this organism (33,106,107).…”
Section: Stress Response Alternative Sigma Factorsmentioning
confidence: 99%